The parameter-space of the three-parameter A2 symmetric flow - Rech P.C.* (2013)
Three two-dimensional parameter planes of a three-parameter, three-dimensional set of autonomous nonlinear first-order differential equations used to model the A2 symmetric flow are investigated. This is done by using the three two-dimensional cross sections of the three-dimensional parameter-space generated by the model. We show that regardless of the two-parameter set considered in the parameter plane plots, all the diagrams present periodic structures embedded in a large chaotic region. We also show that these periodic structures organize themselves in different ways, including sequences whose periods have a well-defined law of formation that can be written in a closed form, and sequences organized in period-adding bifurcation cascades. © 2013 Elsevier Inc. All rights reserved.